Central America and Caribbean food security portal - International Food Policy Research Institute (International Food Policy Research Institute, 2015)
IFPRI’s Spanish-language web portal that focuses on food and nutrition security in Central America. The objective of the portal is to provide a set of indicators on food and nutrition security and early warning mechanisms as well as opportunities for dialogue among policymakers, researchers, the private sector and others seeking to increase the resilience of the world’s poor to possible food-related crises, including price and climate shocks.